2020
DOI: 10.1371/journal.pone.0228631
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal divergence and evolutionary inferences in Pentatomomorpha infraorder (Hemiptera, Heteroptera) based on the chromosomal location of ribosomal genes

Abstract: With the objective of assisting in the understanding of the chromosome evolution of Pentatomomorpha and in the quest to understand how the genome organizes/reorganizes for the chromosomal position of the 45S rDNA in this infraorder, we analyzed 15 species (it has being 12 never studied before by FISH) of Pentatomomorpha with the probe of 18S rDNA. The mapping of the 45S gene in the Coreidae family demonstrated that the species presented markings on the autosomes, with the exception of Acanthocephala parensis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…This terminal location is highly conserved in the infraorder Pentatomomorpha, even in related species that exhibit wide variations in chromosome number; chromosome position of the 18S rDNA sites is commonly subterminal (Bardella et al 2013a). The species E. collaris showed two signals of hybridization in an autosomal bivalent, as previously reported by Souza-Firmino et al (2020).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This terminal location is highly conserved in the infraorder Pentatomomorpha, even in related species that exhibit wide variations in chromosome number; chromosome position of the 18S rDNA sites is commonly subterminal (Bardella et al 2013a). The species E. collaris showed two signals of hybridization in an autosomal bivalent, as previously reported by Souza-Firmino et al (2020).…”
Section: Discussionsupporting
confidence: 81%
“…Signals of 18S rDNA in a single bivalent were observed for all species of this study, and this pattern is commonly found in the species of the Pentatomidae Grozeva et al 2015). Most studies of the Pentatomidae report the presence of this cluster on an autosomal pair (Papeschi et al 2003;Bressa et al 2008Bressa et al , 2009Grozeva et al 2011Grozeva et al , 2015Bardella et al 2013aBardella et al , 2016aSouza-Firmino et al 2020).…”
Section: Discussionsupporting
confidence: 72%
“…Over the past 15 years, several review papers devoted to individual higher taxa of true bugs have been published, namely, Cimicomorpha ( Kuznetsova et al 2011 ), Gerromorpha ( Fairbairn et al 2016 ), and Pentatomomorpha ( Souza-Firmino et al 2020 ). Besides, a great number of research papers have been published too (e.g.…”
Section: Review and Discussionmentioning
confidence: 99%
“…homeologous chromosomes between different species, it is most likely that the same autosomal pair is the carrier of the major rDNA clusters, being the ancestral condition in Triatomini (syntenic location of their rDNA arrays). The autosomal location is by far the most frequent location in other heteropteran families such as Tingidae, Coreidae, Pentatomidae and Pyrrhocoridae (Golub et al, 2018;Souza-Firmino et al, 2020). When rDNA loci appear on the Y chromosome, in general the hybridization signals are smaller than those that appear on the X chromosome, suggesting that the number of copies of rDNA arrays in the Y chromosome is lower than in the X chromosome (Fig.…”
Section: Complexmentioning
confidence: 98%
“…The characterization of the number and distribution of rDNA genes using fluorescence in situ hybridization (FISH) provides suitable landmarks for the construction of physical maps in comparative genomics. These maps have been used to trace evolutionary pathways in several insect groups (Brianti et al, 2009;Ferretti et al, 2019;Sproul et al, 2020;Menezes et al, 2021), including ones with holocentric chromosomes such as Lepidoptera, Odonata and Psocoptera (Golub et al, 2019;Kuznetsova et al, 2020;Provazníková et al, 2021) and several hemipteran groups (Manicardi et al, 2015;Anjos et al, 2018;Golub et al, 2018;Maryańska-Nadachowska et al, 2018;Souza-Firmino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%